2018
DOI: 10.1016/j.actbio.2018.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Cell-laden and orthogonal-multilayer tissue-engineered corneal stroma induced by a mechanical collagen microenvironment and transplantation in a rabbit model

Abstract: The development of functional therapies for corneal repair and regeneration is a pressing issue. Corneal stroma provides the principal functions of the cornea. Here, we have developed a protocol for the efficient generation of a cell-laden and orthogonal-multilayer tissue-engineered (TE) corneal stroma, which is induced by the mechanical effects of compressed collagen (CC) or stretched compressed collagen (SCC). These models facilitate the construction of physiological feature TE corneal stroma, which serves a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 60 publications
1
17
0
Order By: Relevance
“…The RNA-seq analysis was performed as previously described (Cui et al, 2018). Briefly, total RNA of organoids in RPiPSCs and NiPSCs was extracted.…”
Section: Methodsmentioning
confidence: 99%
“…The RNA-seq analysis was performed as previously described (Cui et al, 2018). Briefly, total RNA of organoids in RPiPSCs and NiPSCs was extracted.…”
Section: Methodsmentioning
confidence: 99%
“…Although stromal cells (keratocytes) are dendritic shaped in the native cornea, they shift into spindle-shaped fibroblasts or polygonal corneal myofibroblast in serum. Despite this fact, it is observed that they shift to keratocyte cells in collagen after a week of culture with serum [214]. Cultured keratocyte cells on groove-patterned silk film also elongated towards the grooves and resulted in orderly aligned cells in comparison with cells cultured on unpatterned films.…”
Section: Conclusion and Future Challengesmentioning
confidence: 99%
“…High mechanical strength is essential for the survival of DPS grafts, as they need to withstand the tears caused by stitches tear during the surgery, as well as the membrane stresses caused by intraocular pressure and external forces. 43,44 In vitro, cell phenotypes and behaviors are greatly affected by the molecules released by ECM scaffolds. 45 The scleral ECM protein composition and the growth factor composition in the DPS may contribute to this effect.…”
Section: F I G U R Ementioning
confidence: 99%